Handbook of the international political economy of energy and natural resources - Goldthau, Andreas; Keating, Michael F. 1973-; Kuzemko, Caroline (Handbooks of research on international political economy, 2018)
This Handbook offers a comprehensive overview of the latest research from leading scholars on the international political economy of energy and resources. Highlighting the important conceptual and empirical themes, the chapters study all levels of governance, from global to local, and explore the wide range of issues emerging in a changing political and economic environment